Emergency stay triggered Tako-Tsubo syndrome: A case report and review of the literature - R Bougrine; Y Hdidou; H Aissaoui; N Elouafi; N Ismaili (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
Tako-Tsubo cardiomyopathy is an increasingly recognized as clinical syndrome characterized by transient apical left ventricular dysfunction. An episode of intense emotional of physical stress is reported in many cases prior to presentation. The pathophysiology remains unknown, but high levels of circulating catecholamine are presumed to be the triggering factor and the most favored explanation for this primary acquired cardiomyopathy. We describe the case of 48-year-old women presenting Tako-Tsubo Cardiomyopathy (CTM), triggered 4 hours later during her stay in the emergency department to manage a hypertensive emergency.